Trans fatty acids and saturated fatty acids in margarines and spreads in Kazakhstan: Study period 2015–2021 - Kainaubek Toshtay; Ali Auyezov; Seitkhan Azat; Rosa Busquets (Food Chemistry: X)
Oil and other fat rich products such as some processed foods can contain unhealthy amounts of trans fatty acids (TFA) and saturated fatty acids (SFA). Diets rich in TFA have been linked to coronary artery disease. It is necessary to quantify and police the type of fat in foods to assess its risk. For the first time, this study quantifies the TFA content in margarines and spreads sold in the Kazakhstan markets in the period from 2015 to 2021. Fatty acid composition, and importantly TFA levels, were determined in 6 brands of margarines and 5 brands of spreads used in the food industry and by consumers directly in 2015–2017, and in 23 brands of margarines and 23 brands of spreads from 2018 to 2021. The study margarines and spreads had 20.0 ± 0.02 % TFA on average until 2018. In contrast, in the period 2018–2021, the TFA average content was 14.2 ± 0.06 % in margarines, and 10.6 ± 0.05 % in spreads, which is still 7.4 and 6 times higher than the regulatory requirements of the Customs Union (Kazakhstan, Russia, Belarus, Kyrgyzstan) and the EU, respectively. The strong cause effect between TFA and cardiovascular diseases urges Kazakhstan and other countries to reduce TFA in commercial products. It also encourages research and implementation of technical measures to provide healthy food products that effectively comply with national and international regulations regarding TFA content. The aim of the study was to analyze changes in the quality of solid fat products produced in Kazakhstan over time, particularly after the Technical Regulations of the Customs Union came into effect on January 1, 2018.